Analisis Makna Tanda pada Poster Film Perahu Kertas - Hasbullah Hasbullah; Risyaf Kudus Pranasa (Jurnal SASAK : Desain Visual dan Komunikasi, 2023)
The Paper Boat film is an adaptation of the novel by Dewi Lestari with the youth romance genre which was first published in digital form (WAP) in April 2008, until finally it was successfully published in a book and published in 2009 by Bentang Pustaka. Paper Boat itself is Dee's sixth novel and his first novel with a popular genre. Departing from the background that the researcher described, the researcher is interested in analyzing and dismantling the visual meanings contained in the film poster "Paper Boat" using Charles Sanders Pierce's semiotic analysis method. Because behind the visuals of course there are messages that the poster maker wants to convey, both in the icon, index and symbol. From the results of the analysis, the researchers found that in designing a film poster work (Paper Boat) the poster maker deliberately includes and includes components in the form of signs that have meaning to make a beautiful ornament and can convey the message to be conveyed in a design work.